DEVELOPMENT OF HR SCORECARD, A TOOL FOR MEASURING THE STRATEGY EXECUTION WITHIN HR FUNCTION - Case: M-real - Numminen, Ilkka (My University, 2003)
This master thesis examined the development process of HR scorecard, an approach to measure strategy execution within HR organization, and explored the benefits and obstacles in this creation process. The academic literature has focused on the balanced scorecard concept and operative indicators of human capital, but there has been clear lack of empirical research on strategic HR measurement, and drilling deeper into the different phases of HR performance measurement system. The study used case study research method that had elements of constructive research approach, and draw its findings mostly from the semi-structured interviews of 12 HR professionals. Additional sources such as observations, e-mail surveys and project reports were also used. The results were then categorized by the themes by using qualitative content analysis. Due to an ambiguous and turbulent external environment as well as raise of knowledge society, the scholars have started to emphasise HR as a strategic asset, which should participate in company’s strategy formulation process as an equal business partner. The HR scorecard is one tool to prove the impact of HR, to ensure its effectiveness and efficiency and to follow the implementation of common blueprint. Approach recognizes the value-creating linkages within the firm and balances between intangible and tangible assets, financial and non-financial measures as well as leading and lagging indicators. The creation process lead to development of HR strategy map, identification of critical success factors, formulation of key performance indicators, classification of pros and cons of strategic measures as well as discovery of the bottlenecks and benefits of each development stage. The findings indicate that there are various different bottlenecks in each phase of the project that have to be unravelled to ensure the unproblematic flow of project, and to obtain the benefits of each phase. The scorecard was designed into a template form, as there was need to find a flexible structure with certain static elements. Future scholars could focus on findings evidence about the credibility and effectiveness of this new approach. In addition more understanding of the development project as a whole is needed to guarantee more effective flow of performance measurement projects.
Keywords: HR scorecard; Development process; HR Performance Measurement; Bottlenecks; Alignment; Balanced Scorecard; fi=Johtaminen ja organisaatiot|en=Management and Organization|